Action of 1,25(OH)2D3 on Human Asthmatic Bronchial Fibroblasts: Implications for Airway Remodeling in Asthma - Plesa, Maria; Gaudet, Mellissa; Mogas, Andrea; Olivenstein, Ronald; Saba Al Heialy; Qutayba Hamid (Journal of asthma and allergy, 2020)
Background: Airway fibroblasts are major contributors to the histopathological feature of airway remodeling in asthma by their implication in the cell invasiveness and profibrogenic secretory phenotype observed in subepithelial fibrosis. 1,25 Dihydroxy vitamin D3 (1,25(OH)2D3) is an important therapeutic agent that blocks many features of airway remodeling induced by profibrogenic mediators, such as transforming growth factor beta 1 (TGF-β 1) or T helper type 1 inflammatory cytokines. Objective: We hypothesized that 1,25(OH)2D3 opposes the TGF-β 1 or tumor necrosis factor alpha (TNF-α)-Interleukin 1 beta (IL-1β) stimulation on airway fibroblast profibrogenic secretory phenotype observed in severe asthmatic patients. Our aim was to investigate the anti-fibrogenic effect of 1,25(OH)2D3 in TGF-β 1 or TNF-α-IL-1β-stimulated human bronchial fibroblast cells (HBFCs) from severe asthmatic compared with non-asthmatic subjects. Patients and Methods: All experiments were performed on primary HBFCs from asthmatic (DHBFCs, n=4) and non-asthmatic subjects (NHBFCs, n=4). mRNA expression and protein quantification of key fibrogenic markers were analyzed by RT-qPCR and ELISA, comparing HBFCs from asthmatic and non-asthmatic subjects. Vitamin D receptor (VDR) mRNA expression and its functionality in HBFCs were assessed by RT-qPCR. HBFCs proliferation was assessed by flow cytometry using BrdU-FITC/7AAD bivariate staining, while HBFCs apoptosis by Annexin V-FITC/7AAD. Results: VDR is constitutively expressed in HBFCs and the addition of 1,25(OH)2D3 significantly increased mRNA expression of CYP24A1 (a direct VDRs’ target gene) in both HBFCs groups. DHBFCs cultured in the presence of TGF-β 1 or TNF-α-IL-1β showed increased mRNA expression and protein secretion of fibrogenic markers when compared to NHBFCs. Additionally, we observed decreased mRNA expression of FN 1, LUM, BGN, MMP2, COL5A1, TIMP1 and CC-chemokines (CCL2, CCL5, CCL11) in response to 1,25(OH)2D3 addition to the TGF-β 1 or TNF-α-IL-1β-stimulated HBFCs. Cell culture media obtained from TGF-β 1 or TNF-α-IL-1β-stimulated DHBFCs showed decreased protein secretion (fibronectin 1, lumican, MCP1, RANTES and eotaxin-1) in response to 1,25(OH)2D3 when compared to NHBFCs. 1,25(OH)2D3 inhibited proliferation in TGF-β 1-stimulated HBFCs through G0/G1 cell cycle arrest and these effects were not correlated with the induction of apoptosis. Conclusion: DHBFCs under TGF-β 1 or TNF-α-IL-1β stimulation showed higher fibrogenic capacity when compared to NHBFCs. 1,25(OH)2D3 significantly blocked these effects and highlight 1,25(OH)2D3 as a possible therapeutic target for severe asthma.